Three Topological Indices of Two New Variants of Graph Products. (19th November 2021) - Bilal, Muhammad; Jamil, Muhammad Kamran; Waheed, Muhammad; Alameri, Abdu
Abstract : Graph operations play an important role to constructing complex network structures from simple graphs, and these complex networks play vital roles in different fields such as computer science, chemistry, and social sciences. Computation of topological indices of these complex network structures via graph operation is an important task. In this study, we defined two new variants of graph products, namely, corona join and subdivision vertex join products and investigated exact expressions of the first and second Zagreb indices and first reformulated Zagreb index for these new products.